2009
DOI: 10.1111/j.1365-246x.2009.04210.x
|View full text |Cite
|
Sign up to set email alerts
|

Distortion of the apparentS-wave radiation pattern in the high-frequency wavefield: Tottori-Ken Seibu, Japan, earthquake of 2000

Abstract: S U M M A R YThe distortion properties of the apparent S-wave radiation pattern in the high-frequency seismic wavefield of over f > 2 Hz is investigated using a large number of waveform records of the main shock and 29 aftershocks of the Tottori-Ken Seibu, Japan, magnitude (M w ) 6.6 earthquake in 2000. The dense seismic records from the KiK-net strong motion network show a clear four-lobe pattern in the apparent S-wave radiation pattern in the low-frequency wavefield of f < 2 Hz, and shows an almost isotropic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
97
3

Year Published

2014
2014
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(106 citation statements)
references
References 29 publications
6
97
3
Order By: Relevance
“…Nevertheless the radiation pattern effect, which is clearly observed in our synthetics, might be limited to lower frequency range (<∼1 Hz) in real velocity structures. The theoretical four-lobe S-wave radiation pattern may be limited to low frequencies (< 1 Hz), with an isotropic pattern at high frequency due to the scattering of seismic waves (e.g., Liu and Helmberger, 1985;Takenaka et al, 2003;Takemura et al, 2009). In addition, according to Cho et al (2010), observations suggest that far-field radiation patterns change from a distinct doublecouple pattern, with strong directivity effects at low frequencies (< 1 Hz), to a more isotropic pattern with diminished directivity effects at high frequencies, putting forward the fact that directivity effects are also frequency dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless the radiation pattern effect, which is clearly observed in our synthetics, might be limited to lower frequency range (<∼1 Hz) in real velocity structures. The theoretical four-lobe S-wave radiation pattern may be limited to low frequencies (< 1 Hz), with an isotropic pattern at high frequency due to the scattering of seismic waves (e.g., Liu and Helmberger, 1985;Takenaka et al, 2003;Takemura et al, 2009). In addition, according to Cho et al (2010), observations suggest that far-field radiation patterns change from a distinct doublecouple pattern, with strong directivity effects at low frequencies (< 1 Hz), to a more isotropic pattern with diminished directivity effects at high frequencies, putting forward the fact that directivity effects are also frequency dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Takenaka et al (2003) suggested that the frequencydependent distortion of the S-wave radiation pattern might be caused by the mixing and coupling of the horizontal (S H ) and vertical (S V ) S-waves in the heterogeneous structure near the source region. By analyzing dense KiK-net array observations from the Tottori-Ken Seibu earthquake, Mw 6.6, and its aftershocks, Takemura et al (2009) demonstrated the collapse of the S-wave front due to seismic-wave scattering in a heterogeneous structure and showed that the radiation pattern is more isotropic at high frequencies (>2 Hz). Castro et al (2006) suggested that the S H -wave radiation approaches the theoretical radiation only for frequencies below 0.5 Hz.…”
Section: Do Source Radiation Patterns Explain the Observed Azimuthal mentioning
confidence: 99%
“…Studying the Tottori-Ken Seibu earthquake (6.6 M w ), that occurred in 2000 in Japan, Takemura et al (2009) demonstrated that the S-wave radiation pattern could be affected by medium heterogeneities that scatter seismic waves, generating an isotropic pattern. This physical process is frequency dependent.…”
Section: Physical Interpretationsmentioning
confidence: 99%